1975
DOI: 10.1152/ajplegacy.1975.229.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Spinal autonomic afferents in elicitation of tachycardia in volume infusion in the dog

Abstract: Intravenous infusion of blood (36 ml/kg body wt) elicited tachycardia in artificially ventilated anesthetized dogs with intact autonomic innervation and in dogs with cardiac beta-receptor blockade. In contrast, infusion elicited bradycardia in dogs with section of the spinal cord at C6-C7, and in dogs with combined spinal section and cardiac beta-receptor blockade. The control heart rate was less than or equal to 110 beats/min in all the animals. The presence of infusion-induced tachycardia in dogs with beta-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In fact, it has been shown that, via afferent sympathetic fibres, aortic stretch, simulating an increase in aortic pressure, can produce a pressor reflex (Lioy et al 1974); and that, by the same afferent pathway, volume loading can produce a reflex tachycardia (i.e. the phenomenon first described by Bainbridge, 1915) both in anaesthetized dogs (Gupta, 1975) and in chronic unanaesthetized spinal cats (Bishop, Lombardi, Malliani, Pagani & Recordati, 1976).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been shown that, via afferent sympathetic fibres, aortic stretch, simulating an increase in aortic pressure, can produce a pressor reflex (Lioy et al 1974); and that, by the same afferent pathway, volume loading can produce a reflex tachycardia (i.e. the phenomenon first described by Bainbridge, 1915) both in anaesthetized dogs (Gupta, 1975) and in chronic unanaesthetized spinal cats (Bishop, Lombardi, Malliani, Pagani & Recordati, 1976).…”
Section: Resultsmentioning
confidence: 99%
“…4). Water immersion also increases central blood volume and o 60 120 cardiac filling pressure, suggesting that stimulation of cardiopulmonary receptors decreases plasma renin activity in humans. Kiowski and Julius (73) reported that peripheral venous pooling produced by inflation of congesting cuffs on the thighs increased renin activity in healthy volunteers (Fig.…”
Section: Renin Releasementioning
confidence: 99%
“…In recent years Linden (1975,1975) and his associates have stimulated interest in this field by showing in a long series of experiments that the Bainbridge reflex is mainly due to activation of atrial medullated endings . However, sympathetic afferents from the heart also seem to play a role in the reflex (Bishop et al, 1976;Gupta, 1975). Previously all the reflex effects from stimulation of vagal receptors in the atria had been ascribed to activation of the medullated afferents located at the veinatrial junctions (Paintal, 1973).…”
Section: Reflex Effects From Activation Of Atrial Receptorsmentioning
confidence: 99%